Beban Kerja Yang Tinggi Dapat Menurunkan Kinerja Perawat Di Unit Rawat Inap RSUD Leuwiliang Tahun 2021: A High Workload Can Reduce the Performance of Nurses in the Inpatient Unit of Leuwiliang Hospital in 2021 - Fauziah, Herni Sari (Indonesian Scholar Journal of Nursing and Midwifery Science, 2022)
Introduction: The performance of a nurse can be seen from the quality of health services provided to patients. To improve the quality of health services the workload is a factor that must be considered in order to obtain high work productivity. Methods: This study used a quantitative research design with a cross-sectional method with a population and sample of all nurses serving in the Leuwiliang Hospital inpatient room with a total of 82 nurses with a total sampling technique using a workload questionnaire and a nurse performance questionnaire. The bivariate analysis used is the chi-square test. Results: In the results of this study there is a relationship between workload on nurse performance with a p-value of 0,001 and an OR of 0,049. Discussion: The conclusion of this study is that there is a relationship between workload and the performance of nurses in the inpatient unit of Leuwiliang Hospital in 2021.